2020
DOI: 10.1186/s12913-020-05750-0
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and challenges to integrating mental health into HIV programs in a low- and middle-income country: insights from the Nigeria implementation science Alliance

Abstract: Background In Nigeria, there is an estimated 1.9 million people living with HIV (PLHIV), 53% of whom utilize HIV care and services. With decreasing HIV-related deaths and increasing new infections, HIV with its associated comorbidities continue to be a key public health challenge in Nigeria. Untreated, comorbid mental disorders are a critical but potentially modifiable determinant of optimal HIV treatment outcomes. This study aimed to identify the challenges and opportunities re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…Twenty-eight articles in the review identified barriers to diagnosing NCDs (hypertension and diabetes). 14 , 15 , 20 , 35 61 The included studies reported barriers to and facilitators of diagnosing depression among PLWH. 42 , 50 , 62 73 Two studies reported both NCDs and depression.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Twenty-eight articles in the review identified barriers to diagnosing NCDs (hypertension and diabetes). 14 , 15 , 20 , 35 61 The included studies reported barriers to and facilitators of diagnosing depression among PLWH. 42 , 50 , 62 73 Two studies reported both NCDs and depression.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…26 Several studies have reported various challenges to integrate HIV and mental healthcare. 27,28 Among the challenges are inadequate human and financial resources, dearth of data or evidencebased practices, double burden of stigma, structural challenges and a lack of training on HIV services among psychiatric health providers. 27,28,29,30 Despite these challenges, there is evidence of successful integration of HIV and psychiatric services.…”
Section: Introductionmentioning
confidence: 99%
“…27,28 Among the challenges are inadequate human and financial resources, dearth of data or evidencebased practices, double burden of stigma, structural challenges and a lack of training on HIV services among psychiatric health providers. 27,28,29,30 Despite these challenges, there is evidence of successful integration of HIV and psychiatric services. Currently, in Rwanda, psychiatric patients receive routine screening and counselling for HIV and within-facility initiation for ART for those testing positive.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Limited capacities and resources to identify, diagnose, and treat depressive symptoms within health systems also constrain opportunities to deliver mental health care and supportive services. 15 Oftcited efforts to address psychological distress among CALWH involve family-based interventions (ie, caregiver strengthening and parent-child communication), frequently facilitated by lay service providers such as peers and community health workers. 16 Specialized mental health care and treatment, however, may be needed for CALWH exhibiting more severe manifestations of psychological distress.…”
Section: Introductionmentioning
confidence: 99%
“…Stigma related to mental health disorders can demotivate care-seeking and even interfere with caregiver recognition of psychological distress in children and adolescents. 14,15 Limited capacities and resources to identify, diagnose, and treat depressive symptoms within health systems also constrain opportunities to deliver mental health care and supportive services. 15 Oftcited efforts to address psychological distress among CALWH involve family-based interventions (ie, caregiver strengthening and parent-child communication), frequently facilitated by lay service providers such as peers and community health workers.…”
Section: Introductionmentioning
confidence: 99%